Carbon dots derived from Zingiber officinale Rosc (ginger) with hemostatic effects - Hu, Wen-Jing; Yu, Ai-Qi; Bi, Hai-Zheng; Zhang, Zhao-Jiong; Wang, Zhi-Bin; Wang, Meng; Kuang, Hai-Xue (Frontiers in Molecular Biosciences, 2025)
IntroductionGinger, as a traditional Chinese medicine (TCM), can be used in clinical practice to treat various diseases. The product of ginger processed at high temperatures is called carbonized ginger (CG), which has a hemostatic effect that ginger originally did not have. The purpose of this study is to investigate the hemostatic effect of CG and the substances that exert hemostatic effects.MethodsCG was prepared and successfully obtained CG carbon dots (CG-CDs) from its aqueous solution. After fully characterizing its structural information, the hemostatic effect was evaluated using mouse tail bleeding and liver injury bleeding models, and the clotting time was evaluated using capillary coagulation experiments. In addition, the hemostatic mechanism of CG-CDs was explored.ResultsThe average particle size of CG-CDs was observed to be 4.07 nm and the lattice spacing was 0.216 nm. It was mainly composed of graphite structured carbon, with the main constituent elements being C, N, and O, containing functional groups such as C=N, C=O, and C-OH. The FL spectrum showed that the maximum excitation wavelength of CG-CDs was 360 nm, and the maximum emission wavelength was 470 nm. The QY of CG-CDs was calculated to be 0.45%. CG-CDs shortened bleeding time, reduced bleeding volume, and also shortened the time for blood clotting. With the increase of CG-CDs, the values of FIB gradually increased, and the PT values gradually decreased. In addition, CG-CDs increased PLT count, increased PLT activating factor TXB2, decreased 6-keto-PGF1α, increased PAI-1, and decreased t-PA.ConclusionCG-CDs obtained from CG has hemostatic activity, mainly by activating exogenous coagulation and co-coagulation pathways, increasing PLT count, increasing PLT activating factor TXB2, reducing 6-keto-PGF1α, increasing PAI-1, and reducing t-PA, thereby affecting the fibrinolytic system and other pathways to exert hemostatic effects.